A phylogenetic perspective on foraging mode evolution and habitat use in West Indian Anolis lizards (2008)
Although many descriptive studies of foraging mode have been performed, the factors that underlie the evolution of foraging mode remain poorly understood. To test the hypothesis that foraging mode evolution is affected by habitat use, we analysed two data sets including 31 species of West Indian Anolis lizards. In this genus, the same suite of habitat specialists (or ecomorphs) has evolved on four islands, providing the replication necessary to evaluate the generality of the relationship between foraging mode and habitat use. Using habitat and behavioural data, we conducted phylogenetic comparative analyses to determine whether species of the same ecomorph have evolved similar foraging behaviour and whether differences in foraging mode are associated with differences in habitat use. We found that Anolis species show substantial variation in foraging behaviour, including differences in movement and eating rates. Furthermore, variation among ecomorphs indicates that foraging behaviour is related to habitat use, although the specific environmental factors driving foraging divergence are unclear. Our results show that foraging mode is an evolutionarily labile trait that is influenced by evolution of habitat use.